Calcineurin acts in synergy with PMA to inactivate I kappa B/MAD3, an inhibitor of NF-kappa B. - Frantz, B (1994)
The interleukin-2 (IL-2) promoter consists of several independent T cell receptor (TcR) responsive elements. The induction of promoters dependent on these elements is inhibitable by the immunosuppressants cyclosporin A (CsA) and tacrolimus (FK-506). Calcineurin, a Ca2+/calmodulin-dependent protein phosphatase, is the FK-506- and CsA-sensitive enzyme required for TcR mediated activation of the IL-2 promoter. We report that a constitutively active form of calcineurin partially substitutes for the Ca2+ co-stimulus required to activate the IL-2 promoter elements IL-2A (which binds the factors OAP and Oct-1) and IL-2E (which binds NF-AT), and completely substitutes for the Ca2+ co-stimulus required to stimulate an NF-kappa B-dependent element. Calcineurin stimulates the NF-kappa B element by enhancing inactivation of I kappa B/MAD3, an inhibitor of NF-kappa B, thereby increasing the amount of nuclear NF-kappa B DNA binding activity. These data provide the first demonstration in vivo that activation of a protein phosphatase can inactivate I kappa B, and suggest one possible explanation for mechanism-based toxicities associated with FK-506 and CsA by demonstrating that these drugs can inhibit the calcineurin-dependent activation of a virtually ubiquitous transcription factor.